ANALISIS PENDEKATAN STEAM BERBASIS MEDIA BUSY BOOK (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This study aims to analyze the STEAM approach based on Busy Book media in increasing learning effectiveness. We will explore the effect of using Busy Books on students' conceptual understanding, learning motivation, critical thinking skills, and problem solving abilities. In addition, we will also identify the advantages and limitations of this approach. In this study, we will use a qualitative research method with a literature study approach. Literature study, also known as literature review or literature review, is a systematic process of gathering, evaluating, and analyzing literature sources that are relevant to a particular research topic. A literature study is conducted to gain a comprehensive understanding of previous research, existing thoughts and findings, and knowledge gaps that still need to be filled.